(Ideological opinions for Al-Imaam Sahl bin Abd-Allah Altostery in the judiciary and destiny –Collection and Study) (Islamic Sciences Journal, 2023)
This paper (Ideological opinions for Al-Imaam Sahl bin Abd-Allah Altostery in the judiciary and destiny – Collection and Study) is divided  into two  parts that was preceded with (Definition of the judiciary and destiny in language and idiom ,The difference between them and rank of destiny) andI divided  this research into tree demands In first demand I showed definition of the judiciary and destiny in language and in idiom, in second demand  Difference between the judiciary and destiny while in third demand the rank of destiny.The second research  (Ideological opinions for Al-Imaam Sahl bin Abd-Allah Altostery in the judiciary and destiny) that was divided into tree demand.In first demand I showed opinions for Al-Imaam Sahl bin Abd-Allah Altostery in thefaith with judiciary and destiny, In the second demand opinions for Al-Imaam Sahl bin Abd-Allah  Altostery  about god will  faith with judiciary and destiny while In third demand was about opinions for Al-Imaam  Sahl bin Abd-about chosing the things, run them and  rulling  them by god.I was finished the study by conclusion that has contained all important   results in this study then follewe the conclusion with references.